The Impact of Modifiable Preoral Factors on Swallowing and Nutritional Outcomes in Healthy Adults: A Scoping Review. - Burdick, Ryan; Bayne, David; Hitchcock, Mary; Gilmore-Bykovskyi, Andrea; Shune, Samantha; Rogus-Pulia, Nicole (Journal of Speech, Language & Hearing Research, 2023)
Purpose: Swallowing has previously been characterized as consisting of four phases; however, it has become apparent that these four phases are not truly discrete and may be influenced by factors occurring prior to bolus entrance into the oral cavity (i.e., preoral factors). Still, the relationship between these factors and swallowing remains poorly understood. The aim of this review was to synthesize and characterize the literature pertaining to the influence of preoral factors on swallowing and nutritional outcomes in healthy individuals. Method: We performed a scoping review, searching the databases of PubMed, CINAHL, Cochrane, and Scopus. Search terms included those related to swallowing, experience of preoral factors, and exclusionary terminology to reduce animal and pediatric literature. Our initial search revealed 5,560 unique articles, of which 153 met our inclusionary criteria and were accepted into the review. Results: Of the accepted articles, 78% were focused exclusively on nutritional outcomes, 17% were focused on both swallowing and nutritional outcomes, and 5% were focused on solely swallowing outcomes. Of the preoral factors examined, 99% were exteroceptive in nature (17% olfactory, 44% visual, 21% auditory, 7% tactile, 11% other), while 1% were proprioceptive in nature. Conclusions: This review supports the influence of preoral factors on swallowing and nutritional outcomes. However, there is a large emphasis on the visual modality and on nutritional outcomes. Nearly none of the literature found in this review directly measured swallowing safety, efficiency, or physiology. Future work will benefit from a larger focus on proprioceptive preoral factors as they relate to swallowing outcomes.